Effects of lift-up design on pedestrian level wind comfort in different building configurations under three wind directions. (15th May 2017) - Du, Yaxing; Mak, Cheuk Ming; Liu, Jianlin; Xia, Qian; Niu, Jianlei; Kwok, K.C.S.
Abstract: The pedestrian level wind environment is seriously deteriorated by moderated local wind flow in a densely built-up subtropical city like Hong Kong. In order to improve the weak wind condition, the lift-up design has been used for some time. However, there is a lack of understanding and quantitative assessment of its modification on the pedestrian level wind comfort around different building configurations under different wind directions. This paper aims to study the effects of lift-up design in four common building configurations on the wind comfort via computational fluid dynamics (CFD) simulations. The turbulence model and numerical method are firstly validated by comparing the simulated wind flow data with the wind tunnel test results. The validated model is then utilized to simulate the four building configurations, including the "─", "L", "U" and "□" shaped buildings. The mean wind velocity ratio ( MVR ) and mean wind velocity change ratio ( Δ MVR ) are employed to identify the wind comfort and to quantitatively evaluate the improvements due to the lift-up design. Results show that the lift-up design can improve the wind comfort in building surroundings and its influence is highly dependent on the incident wind direction. Specifically, the wind comfort is better under the oblique wind direction than the other two wind directions. These findings can provide us a better understanding of the lift-up design and will be helpful in better precinct planning. Highlights: The wind flow around buildings are studied using CFD method under three wind directions. The wind comfort around the "─", "L", "U" and "□" shaped buildings with lift-up design are evaluated. The modifications of flow pattern due to lift-up design are quantitative analysed by mean wind velocity change ratio. The lift-up design helps in improving wind comfort around buildings and the effects depend on approaching wind directions.